Uranium-mediated carbon dioxide activation and functionalization - Lam, Oanh P.; Meyer, Karsten (Polyhedron, 2012)
The importance of CO activation and functionalization is undeniable, given the surge of effort in this area in the last few decades. Uranium complexes have begun to emerge as excellent candidates for small molecule activation, often exemplified by their varied and unprecedented chemistry with CO . In this review, we present accounts of carbon dioxide activation and functionalization mediated by uranium complexes in various oxidation states from low-valent (+3), mid-valent (+4), to high-valent (+5). © 2011 Elsevier Ltd. All rights reserved.